1999
DOI: 10.1159/000021292
|View full text |Cite
|
Sign up to set email alerts
|

Simple Chemiluminescence Assays for Free Radicals in Venous Blood and Serum Samples: Results in Atopic, Psoriasis, MCS and Cancer Patients

Abstract: Objective: To investigate the generation of reactive oxygen species (ROS) in serum and venous blood as well as the serum antioxidative activity (AOA) in patients and healthy controls by means of a simplified chemiluminescence (CL) methodology. Study Participants:48 Atopic eczema, 23 psoriasis, 15 multiple chemical sensitivity (MCS) and 35 cancer patients together with 22 healthy volunteers. Methods:ROS generation/photon emission in blood and serum samples under basal conditions and after light exposure as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…On the other hand, compounds 8d, 8e, and 10 did not exhibit inhibitory activity at this dose. From these results, it was suggested that the phenyl group for R 1 and the hydrogen atom for R 3 were needed for exhibiting the inhibitory activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, compounds 8d, 8e, and 10 did not exhibit inhibitory activity at this dose. From these results, it was suggested that the phenyl group for R 1 and the hydrogen atom for R 3 were needed for exhibiting the inhibitory activities.…”
Section: Resultsmentioning
confidence: 99%
“…Proton NMR spectra were recorded on a JEOL GSX270 FT NMR spectrometer. Chemical shifts were given in parts per million (ppm) using tetramethylsilane as the internal standard for spectra obtained in DMSO-d 6 or CDCl 3 . TOF MS (time-of-flight mass spectrometry) was recorded on a Compact MALDI 3 V4.0.0 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…In one study, several antioxidants were used to treat patients with MCS, with some apparent success,23 suggesting that oxidative damage may have a role in MCS. The blood of MCS patients was reported, in a recent study, to have elevated levels of oxidants and the serum to have lower levels of anti‐oxidants, as compared with controls,24 providing substantial evidence for elevated oxidative damage.…”
Section: Evidence From Mcs Patients and Tissue Studiesmentioning
confidence: 99%
“…This is important especially for the larger molecular mass of Hp2-2 (170−900 kDa), since current data about hemoglobin-binding capacity (HBC), the lowest found in Hp2-2 subjects, of various phenotypes are based on immunomethods. In these methods, the serum Hp concentration is generally underestimated because the diffusion of immune complexes is impaired in gels. , Recently, CL signals of free radicals of proteins have been reported, which provides a potential route for exploring the enhancement of CL signals instead of horseradish peroxidase that is used in CL immunoanalysis. We investigated the enhancement by ammonium persulfate of the CL detection of Hp without Western blotting.…”
mentioning
confidence: 99%